The Place and Role of Professional Legal Consciousness in Various Legal Activities - KOVALSKA, Vita Volodymyrivna (Journal of Advanced Research in Law and Economics, 2017)
The paper defines the content of the concepts of ‘professional legal consciousness’ and ‘legal activities.’ It also analyzes the place and role of professional legal consciousness within the structure of legal activities. In addition, it describes the specifics of interaction of professional legal consciousness and legal activities and clarifies the importance of legal consciousness at various stages of legal regulation. It is emphasized that effective lawmaking and law-enforcement activities are not possible without professional legal consciosuness . The paper defines the content of the concepts ‘professional legal consciousness’ (that can be examined as from positions of activity in the field of a law) and ‘legal activity’ - activity of all subjects on realization of rights and duties through special legal facilities in the different types of the legal adjusting: the right to create, to interpret, control and other activity). An analysis of the place and significance of professional legal consciousness in the structure of legal activity is performed. Features of co-operation of professional sense of justice and legal activity are analyzed, the value of sense of justice is described, on the different stages of the legal adjusting. Determining the features of co-operation of sense of justice and legal activity, it is necessary to notice that they fall neither into the category of legal facilities nor to the structural mechanisms of the legal adjusting, however, inflict ponderable influence and provide functioning of all stages last, and by sense of justice there is a process of awareness of legal facilities, their including to the structure of legal. It is underlined in the article, that effective right to create and apply activity is impossible without professional sense of justice, as professional sense of justice inflicts general influence on all process of forming of right, plays a considerable role not only on the stage of direct right to create but also on the stage of right to create, taking part in forming of legal ideas, looks, influenced, that remove the necessity of changes for the operating legal adjusting. Professional sense of justice, from point of depth of cognition of the legal phenomena and processes, shows by itself legal knowledges, skills, persuasions, senses which right to create activity is carried out by, are specialized. Thus, it is necessary to mark that all specific elements which make the structure of professional sense of justice have own meaningfulness on the different areas of right to create.